Penerapan Sanksi Hukum Terhadap Pelanggaran Standar Laik Operasi Kapal Nelayan Di Perairan Tapanuli Tengah - Sarma Winalda Siregar (UM.Tapanuli Selatan, 2024)
Operational Worthiness Standard (SLO) is one of the instruments in fisheries supervision in accordance with the Regulation of the Minister of Maritime Affairs and Fisheries Number 23 of 2021. PERMEN-KP No. 23 of 2021 is a replacement regulation for PERMEN KP No. 1 of 2017 concerning the Certificate of Operational Worthiness of Fishing Vessels. The vessel is considered unfit for operation because it is proven not to meet the requirements of the provisions set, namely the existence of an expired ship certificate, inadequate safety equipment, the ship's registration mark is not installed, the load is excessive/over draft, the load does not match the cargo document and so on which will have fatal consequences if the ship continues to sail or operate. This study uses a normative juridical legal research type. The results of the study show that the Tapanuli Tengah Waters Police Headquarters Unit is still seeking action preventive and preemptive when in the middle conducting inspections in waters in the context of sea patrols or by socializing the law to the fishing community or the community when carrying out sambaing activities, then the obstacles for the Water Police Unit in implementing legal sanctions for violations are internal factors from the ranks of the Water Police itself, due to the lack of personnel and ship facilities owned. The personnel of the Tapanuli Tengah Polairud Police only number 8 (eight) people including